2019
DOI: 10.1002/hbm.24844
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and vascular risk factors are associated with reduced cerebral blood flow and poorer midlife memory performance

Abstract: Midlife metabolic and vascular risk factors (MVRFs) predict cognitive decline and dementia; however, these risk factors tend to overlap, and the mechanisms underlying their effects on cognitive performance are not well understood. This crosssectional study investigates the contributions of MVRFs to regional cerebral blood flow (CBF) and verbal learning & memory among middle-aged adults. We used partial least squares (PLS) analysis to create latent risk factor profiles and examine their associations to CBF in 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
(94 reference statements)
0
12
0
Order By: Relevance
“…Improvements in adiposity and body weight, blood pressure, blood lipids, glucose metabolism and insulin sensitivity have been reported in association with adherence to the Mediterranean diet [ 72 , 92 , 93 , 94 ]. These effects may beneficially affect brain function, cognition, and mood [ 95 , 96 , 97 ], which are also important to sleep.…”
Section: Potential Mechanisms Underlying the Mediterranean Diet Effec...mentioning
confidence: 99%
“…Improvements in adiposity and body weight, blood pressure, blood lipids, glucose metabolism and insulin sensitivity have been reported in association with adherence to the Mediterranean diet [ 72 , 92 , 93 , 94 ]. These effects may beneficially affect brain function, cognition, and mood [ 95 , 96 , 97 ], which are also important to sleep.…”
Section: Potential Mechanisms Underlying the Mediterranean Diet Effec...mentioning
confidence: 99%
“…In summary, imaging studies in AD have shown that dysregulation for CBF and rCBV are critically involved in the pathogenesis of the disease. Changes in rCBF occur earlier than rCBV during the disease course [98], where metabolic and vascular risk factors have been implicated as a driver of hemodynamic disturbances [102,103]. Consistent, experimental studies have shown that these risk factors compromises cerebral perfusion, contribute to cognitive impairment and enhances AD pathology [104,105].…”
Section: Dysregulation Regional Rcbf and Volumementioning
confidence: 99%
“…our study did not support a significant mediation effect of relevant brain structural measures (e.g., hippocampal and WM volumes) in the associations between serum lipids (e.g., HDL-C) and cognitive phenotypes. This suggests that additional pathways, such as reduced cerebral blood flow [34], might be involved in the cognitive consequences associated with abnormal serum lipid profiles, which deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is biologically plausible to hypothesize that abnormal serum lipids might be linked to cognitive outcomes in old age via affecting brain amyloidβ protein deposition [31] and cerebrovascular disease [32,33], our study did not support a significant mediation effect of relevant brain structural measures (e.g., hippocampal and WM volumes) in the associations between serum lipids (e.g., HDL-C) and cognitive phenotypes. This suggests that additional pathways, such as reduced cerebral blood flow [34], might be involved in the cognitive consequences associated with abnormal serum lipid profiles, which deserves further investigation.…”
Section: Ta B L Ementioning
confidence: 99%